The Impact of AI-Based Social Media on Users’ Material Dimension - Arkhipova , Daria (E|C, 2023)
This research delves into the physical implications of digital communication, with a specific focus on social media platforms that utilise Artificial Intelligence recommendation systems (AiRS). AiRS continually provide stimuli to users, encouraging their interactions with digital representations of everyday material objects. These AI- mediated representations have the potential to influence users’ behaviours and physical states, bridging the gap between the digital and the material, natural environments. The primary objective of this study is to establish a methodological framework for investigating how digital platforms can shape users’ interactions with AI-mediated digital representations and their material world objects. Furthermore, this research views digital platforms as environments capable of providing affordances to users and fostering scaffolding processes through interactions within the environment. The impact of AI-mediated social media on its users is examined by establishing connections between methodologies from cognitive science and semiotics, aiming to gain a comprehensive understanding of how these platforms influence users’ experiences and behaviours in both the digital and physical realms.